To the problem of formation of the lingual skills of the secondary lingual personality based on the conceptual construction (Eurasian Journal of Philology Science and Education, 2016)
Current problem in the theory and practice of teaching language as a secondary is an issue of intercultural communication of the native speakers of different languages and cultures, who are learning a second language. The authors of the article set a task to analyze the verbal behavior of foreigners studying Russian and Kazakh languages, based on the introspective analysis of the native speakers. An analysis of the verbal behavior is based on the algorithm of the organization and systematization of certain concepts in the thematical conceptual constructions. Creation of a base of algorithms of speech behavior forming, learning to use the algorithms is one of the methodical techniques of forming of the secondary lingual personality.
Keywords: concept; conceptual construction; algorithm of verbal behavior; verbal behavior strategy; native speaker; secondary lingual personality